TECHNOLOGICAL PROPOSAL FOR THE PRODUCTION OF TRIPLE SUPERPHOSPHATE - Serrano Castillo, Jenny; Iraola Reyes, Teresa de la Caridad; Ramos Miranda, Fernando (Centro Azúcar Journal, 2024)
Introduction: Over time the human population increases and sites suitable for cultivation are required to increase their production, find new sites to satisfy the needs, or rotate crops on the same plot of land. With the aim of making crops more intensive, fertilizers and chemical fertilizers appear. Objective: To present the economic impact assessment of the technological design of a facility producing triple superphosphate (TSP) from imported or national phosphate rock and imported phosphoric acid. Materials and Methods: Starting from the technological design of an industrial facility based on a technology recommended in scientific-technical literature, material balances are carried out and investment costs and production costs are determined to estimate the selling prices of the product and the dynamic indicators for the proposed investment. Results and Discussion: The economic analysis determined that there were losses between 4.6 and 28.86% in three of the percentages studied due to the price of phosphoric acid, so 70% was evaluated which was the only variant that showed positive results so the dynamic values of profitability Net Present Value, Internal Rate of Return, and Discounted Payback Period at Discounted were calculated for that percent. Conclusions: Technologically, the production of triple superphosphate is feasible using partial proportions between 70 and 78% of phosphoric acid, although the best conditions of dynamic indicators are reported at 70%.